2007
DOI: 10.1007/s00104-006-1284-2
|View full text |Cite
|
Sign up to set email alerts
|

Elastic titanium nails in minimally invasive osteosynthesis for midclavicular fractures

Abstract: Intramedullary stabilisation of mid-clavicular fractures with titanium elastic nails is a minimally invasive technique with good functional results. Patients must be informed about the possibility of open reduction in about half of the cases as well as shoulder asymmetry, migration of the nail, and iatrogenic nerve and vessel injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(69 reference statements)
0
3
0
9
Order By: Relevance
“…14,[23][24][25][26][27][28][29][30][31][32] In addition, 6 studies included treatment of nonunions or delayed unions and did not make a distinction with the treatment of acute fractures when describing the complications, 16,33-37 2 studies were surgical technique papers, 38,39 1 study reported on plate fixation, 40 1 study lacked a definition for dislocation, 41 1 study did not make a distinction between angulation and comminution, 42 1 study included fewer than 10 patients 15 and, in 1 study, 11 authors reported on a previously reported patient population. Reported rates for major complications like bonehealing problems and deep infections requiring implant removal were no higher than 7%.…”
Section: Discussionmentioning
confidence: 99%
“…14,[23][24][25][26][27][28][29][30][31][32] In addition, 6 studies included treatment of nonunions or delayed unions and did not make a distinction with the treatment of acute fractures when describing the complications, 16,33-37 2 studies were surgical technique papers, 38,39 1 study reported on plate fixation, 40 1 study lacked a definition for dislocation, 41 1 study did not make a distinction between angulation and comminution, 42 1 study included fewer than 10 patients 15 and, in 1 study, 11 authors reported on a previously reported patient population. Reported rates for major complications like bonehealing problems and deep infections requiring implant removal were no higher than 7%.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of intramedullary devices (e.g. titanium elastic nailing) include them being minimally invasive and a low cost, with shoulder mobilisation at an early stage [15,16]. Thus, different internal fixation devices have their own merits.…”
Section: Introductionmentioning
confidence: 99%
“…Als Implantat wurde neben einer 3,5-mm-Zugschraube eine winkelstabile Kleinfragmentplatte aus Reintitan (Firma DePuy Synthes, Bochum) verwendet (l " Abb. 2 Abstract ! A 32-year-old patient suffered from progredient intermittent claudication of the left arm 6 months after plate fixation of a midshaft clavicular fracture (OTA classification type A).…”
unclassified
“…Die Klavikulafraktur ist mit einem Anteil von 5-12 % beim Erwachsenen eine häufige Verletzung. In 65-81% ist das mittlere Drittel betroffen [2]. In vielen Fällen können diese Frakturen konservativ mit guten funktionellen Ergebnissen zur Ausheilung gebracht werden [3].…”
unclassified